Evaluation of synergic effects of iodixanol and trehalose on cryosurvival of electroejaculated ram semen - Ozmen, Mehmet Ferit; Cirit, Umut; Arici, Ramazan; Demir, Kamber; Kurt, Dogan; Pabuccuoglu, Serhat; Ak, Kemal (Wiley, 2020)
The primary aim of the study was to investigate whether iodixanol and trehalose would have a synergic effect on the cryosurvival of electroejaculated ram semen. Tris-based diluter was used to prepare 9 different extenders by the addition of iodixanol or trehalose alone or varying combinations of these substances. Diluters were prepared as follows: Tris (control), Io5 (5% iodixanol), Tr25 (25 mmol/L trehalose), Tr50 (50 mmol/L trehalose), Tr50 + Io1.25 (50 mmol/L trehalose and 1.25% iodixanol), Tr50 + Io2.5 (50 mmol/L trehalose and 2.5% iodixanol), Tr50 + Io5 (50 mmol/L trehalose and 5% iodixanol), Tr25 + Io5 (25 mmol/L trehalose and 5% iodixanol) and Tr12.5 + Io5 (12.5 mmol/L trehalose and 5% iodixanol). Supplementation of the freezing extender with trehalose or iodixanol alone supported the protection of both morphological and functional integrity of ram spermatozoa and total motility at 1 and 4 hr post-thawing respectively. However, beyond these positive effects, the combination of trehalose (25 mmol/L) and iodixanol (5%) significantly increased post-thaw sperm longevity and motion properties at the end of 4-hr incubation. The results of the study clearly showed that there was positive synergic effect of iodixanol and trehalose on cryosurvival of ram semen.
Keywords: electroejaculated semen; freezing; iodixanol; ram; trehalose